2016
DOI: 10.1021/acs.macromol.5b02470
|View full text |Cite
|
Sign up to set email alerts
|

Order–Order Morphological Transitions for Dual Stimulus Responsive Diblock Copolymer Vesicles

Abstract: A series of non-ionic poly(glycerol monomethacrylate)–poly(2-hydroxypropyl methacrylate) (PGMA–PHPMA) diblock copolymer vesicles has been prepared by reversible addition–fragmentation chain transfer (RAFT) aqueous dispersion polymerization of HPMA at 70 °C at low pH using a carboxylic acid-based chain transfer agent. The degree of polymerization (DP) of the PGMA block was fixed at 43, and the DP of the PHPMA block was systematically varied from 175 to 250 in order to target vesicle phase space. Based on our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
121
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(138 citation statements)
references
References 87 publications
9
121
1
7
Order By: Relevance
“…Variable‐temperature 1 H NMR analysis revealed that the degree of hydration of the PHPMA block varied with temperature, leading to a subtle alteration in the packing parameter and thus a morphological transition between worms and spheres. Later, a pH‐responsive mechanism based on ionization of a single end‐group, such as carboxylic acid or morpholine, to change the morphologies was reported. Ionization of a polymer end‐group with a minimum use of base or acid induced a sufficient change in the hydration degree of the PHPMA block and thus the packing parameter, leading to a pH‐responsive morphological transition.…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
See 1 more Smart Citation
“…Variable‐temperature 1 H NMR analysis revealed that the degree of hydration of the PHPMA block varied with temperature, leading to a subtle alteration in the packing parameter and thus a morphological transition between worms and spheres. Later, a pH‐responsive mechanism based on ionization of a single end‐group, such as carboxylic acid or morpholine, to change the morphologies was reported. Ionization of a polymer end‐group with a minimum use of base or acid induced a sufficient change in the hydration degree of the PHPMA block and thus the packing parameter, leading to a pH‐responsive morphological transition.…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
“…Ionization of a polymer end‐group with a minimum use of base or acid induced a sufficient change in the hydration degree of the PHPMA block and thus the packing parameter, leading to a pH‐responsive morphological transition. On the basis of the primary thermally responsive behavior of PHPMA‐based nano‐objects, PGMA−PHPMA vesicles with pH‐responsive end‐groups were reported to exhibit complex stimulus‐responsive behavior, which critically depended on PHPMA DP, pH, and temperature …”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
“…Using 3‐aminophenylboronic acid as binding agent to the pendent cis ‐diol groups of PGMA allowed the phase transition of vesicles with thicker walls to worms at specific DP n,PHPMA . Compared with the end group–driven phase transition of similar nanoobjects described above, that is, HOOC‐PGMA‐ b ‐PHPMA, lateral‐group functionalization showed a higher transition rate and efficiency. The in situ release of encapsulated silica NPs with 20 nm of diameter through vesicle dissociation was also demonstrated at a controlled rate by varying the solution pH and/or 3‐aminophenylboronic acid concentration.…”
Section: Reactive Pisa Nanoobjectsmentioning
confidence: 96%
“…Lovett et al. presented the synthesis of poly(glycerol monomethacrylate)‐ block ‐poly(2‐hydroxylpropyl methacrylate) (PGMA‐ b ‐PHPMA) diblock copolymer vesicles by aqueous RAFTPISA ( Scheme ) using carboxylic acid–functionalized RAFT agent 4 (Scheme ) . With a PGMA of low degree of polymerization ( DP n,PGMA = 43), vesicles can be obtained with DP n,PHPMA = 175, 200, 225, and 250.…”
Section: Reactive Pisa Nanoobjectsmentioning
confidence: 99%
See 1 more Smart Citation